A Belgian View of (the Debate on) ‘Dat nooit meer’ – ‘Never Again’ - Koen Aerts (BMGN: Low Countries Historical Review, 2013)
While the booming field of memory studies is characterised by a lack of uniform and consistent methodology, Dat nooit meer [Never Again] seems to reject any theoretical analysis whatsoever. The author, Chris van der Heijden, relies on the journalistic motto ‘show, don’t tell’. Such a vision provides both the strength and the weakness of the argument. On the one hand he manages to dig up a wealth of empirical information; on the other hand, the evidence of his thesis is solely dependent on the selection of sources by the author.   This book therefore is not only a challenge for Dutch war historiography, but also indirectly an urgent call for self-reflection on the international research on collective memories. To what extent is its associative and anecdotal argument a relevant interpretation of how Dutch society remembered and rewrote the past World War II? To what extent can we develop an epistemologically justified and adequate methodology that allows the analysis of the genesis of a collective memory?   This review is part of the discussion forum 'Dat nooit meer' (Chris van der Heijden).